2017
DOI: 10.1038/srep43555
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequences of three Clade 3 Clostridium difficile strains carrying binary toxin genes in China

Abstract: Clostridium difficile consists of six clades but studies on Clade 3 are limited. Here, we report genome sequences of three Clade 3 C. difficile strains carrying genes encoding toxin A and B and the binary toxin. Isolates 103 and 133 (both of ST5) and isolate 106 (ST285) were recovered from three ICU patients. Whole genome sequencing using HiSeq 2500 revealed 4.1-Mb genomes with 28–29% GC content. There were ≥1,104 SNP between the isolates, suggesting they were not of a single clone. The toxin A and B gene-carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Like the PaLoc reported in other clade 3 strains before [16,33,42], the PaLoc carried by the three ST201 strains discussed in this study as well as another clade 3 strain ZJCDC-S82 contained a mobile genetic element designated Tn6218 inserted between tcdE and tcdA ( Figure 2). It is suggested that the insertion of Tn6218 in PaLoc is clade-specific [16]. Consistence with this, this insertion element was not found in the PaLoc of R20291 in clade 2 and M120 in clade 5.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Like the PaLoc reported in other clade 3 strains before [16,33,42], the PaLoc carried by the three ST201 strains discussed in this study as well as another clade 3 strain ZJCDC-S82 contained a mobile genetic element designated Tn6218 inserted between tcdE and tcdA ( Figure 2). It is suggested that the insertion of Tn6218 in PaLoc is clade-specific [16]. Consistence with this, this insertion element was not found in the PaLoc of R20291 in clade 2 and M120 in clade 5.…”
Section: Discussionsupporting
confidence: 64%
“…What is more, the clade 3 branch also included another China-sourced toxigenic C. difficile strain ZJCDC-S82 which is also reported as a severe diarrhea-associated strain [42]. In addition, the other three recently-reported binary toxin-positive C. difficile (strains 103, 133, and 106) recovered from three ICU patients in China are also clade 3 strains [16]. These findings suggest that C. difficile clade 3 strains might contribute to CDI outbreak in China.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Data on C. difficile strains in clade 3 with binary toxins are not well documented in mainland China. WGS of three clade 3 C. difficile strains carrying binary toxin genes in a university hospital found that clade 3 has unusual clade-specific PaLoc characteristic of Tn6218 insertion, which may be the main feature to distinguish clade 3 from other C. difficile [41]. The identification of seven novel RTs indicated the diversity of C. difficile strains in this hospital.…”
Section: Discussionmentioning
confidence: 87%